Modern Approaches to Evaluating the Effectiveness of Higher Education Programs - Konurbayeva, Zh.T.; Denissova, O.K.; Nurekenova, E.S. (BUKETOV BUSINESS REVIEW, 2021)
Object: The application of modern approaches to assessing the effectiveness of academic programs in the university is a key task of the higher education management, ensuring the quality of the educational process and the formation of professional competencies of graduates. Methods: The study included methods of systematizing the information of the analyzed literature sources, among them analysis, synthesis, structuring. Methods of expert evaluations were also applied, the peculiarity of which lies in the scientific understanding of the organization of all stages of the examination, as well as in the application of quantitative methods at each stage. The analytical part of this study was based on the use of statistical methods of data processing. Results: The proposed methodology for assessing the effectiveness of educational programs has been tested in the bachelor’s academic programs of D. Serikbayev East Kazakhstan Technical University. This methodology makes it possible to assess the demand for educational programs on qualitative and quantitative parameters and to develop management decisions to develop their potential. Conclusions: The study of domestic and foreign experience allowed recognizing many problems of methodological nature in the field of modern approaches to assess the effectiveness of academic programs of higher education institutions and propose modern methods of their evaluation.